12th European Conference on Antennas and Propagation (EuCAP 2018) 2018
DOI: 10.1049/cp.2018.0779
|View full text |Cite
|
Sign up to set email alerts
|

Selective Excitation of Characteristic Modes on an Electrically Large Antenna for MIMO Applications

Abstract: The selective excitation of individual characteristic modes for MIMO applications on an electrically large antenna structure is investigated. The characteristic mode analysis yields that a large number of modes is significant and thus basically suited for use in a multi-mode antenna. In order to find appropriate excitation arrangements for the individual characteristic modes, they are grouped according to their symmetry properties. It is found that characteristic currents belonging to the same group are correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…The achievable gain is represented by Fig. 4, curve (6). It is shown that by combining the ports of the antenna and using constructive interference, an additional gain of up to two decibel can be achieved.…”
Section: System Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…The achievable gain is represented by Fig. 4, curve (6). It is shown that by combining the ports of the antenna and using constructive interference, an additional gain of up to two decibel can be achieved.…”
Section: System Evaluationmentioning
confidence: 99%
“…The number of significant modes depends on the electrical size of the antenna. As another example, the chassis of a typical modern smart phone is electrically large in the frequency range from 6 GHz to 8.5 GHz and thus exhibits a large number of significant characteristic modes, offering a great diversity potential [6].…”
Section: A Mobile Terminal Antennamentioning
confidence: 99%
“…Towards UWB and multi-mode capability, an electrically large aperture is necessary to enable different current distributions at the same time. As the feeding network connects feeding points and antenna input ports in a sophisticated manner [5], [6], each physical port corresponds to a unique group of modes, which can be excited. Since the groups of modes are orthogonal among each other, the ports are uncoupled.…”
Section: Basics Of Weighted Mode Combiningmentioning
confidence: 99%
“…In the numerical results presented below, focus will be on the planar multi-mode antenna design presented in [5], [6]. So far, this antenna type has been investigated for communication and localization purposes.…”
Section: Introductionmentioning
confidence: 99%
“…A suitable choice of significant CMs and their excitation method can yield antenna designs that meet tough requirements, e.g., [3]. However, electrically large structures lead to large mesh sizes and large increases in the number of significant modes [4]. Thus, CM analysis (CMA) of the full structure is not only computationally demanding, but more importantly the cost is high for finding a subset of modes that are relevant for the antenna design problem at hand.…”
Section: Introductionmentioning
confidence: 99%